Air-stable doping of Bi2Se3 by MoO3 into the topological regime - Edmonds, M.; Hellerstedt, J.; Tadich, A.; Schenk, A.; O'Donnell, Kane; Tosado, J.; Butch, N.; Syers, P.; Paglione, J.; Fuhrer, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
We study vacuum deposition of molecular MoO3 as an acceptor surface transfer dopant for topological insulator Bi2Se3. We perform high-resolution photoelectron spectroscopy on in-situ cleaved Bi2Se3 single crystals and in-situ transport measurements on Bi2Se3 films grown by molecular beam epitaxy. MoO3 is an efficient acceptor, lowering the surface Fermi energy to within -100 meV of the Dirac point, in the topological regime. A 100 nm MoO3 film provides an air-stable doping and passivation layer.